Ayurpharmacoepidemiology en Route to Safeguarding Safety and Efficacy of Ayurvedic Drugs in Global Outlook. (April 2017) - Debnath, Parikshit; Banerjee, Subhadip; Adhikari, Anjan; Debnath, Pratip K.
Ayurpharmacoepidemiology is a new field developed by synergy of the fields of clinical pharmacology, epidemiology, and ayurveda. It will use the effects of ayurvedic medicinal products on large populations to describe and analyze the practices, evaluate the safety and efficacy, and carry out medicoeconomic evaluations. Good pharmacoepidemiology practices in ayurveda is projected to assist with issues of ayurpharmacoepidemiologic research. The embraced good pharmacoepidemiology practices guideline in this viewpoint will be able to provide valuable evidence about the health effects of ayurvedic herbs/drugs and consider different fields like pharmacovigilance, pharmacoeconomics, and drug discovery with ayurvedic reverse pharmacology approach, also pass out significant data for further basic sciences study in ayurveda biology, ayurgenomics, ayurnutrigenomics, and systems biology. Several unanswered questions about ayurvedic drug use and informed interventions or policies that can be addressed by informatics database, which will eventually demonstrate the credibility and rationality of ayurceuticals in the future.